Environmental impact reduction in a pump sub assembly using alternate material. (2020) - Prathap, P.; Madhu, S.; Jayakumar, V.; Tamil Selvam, N.
Abstract: This work addresses the results developed by the systematic method with environmental consciousness in the selection of alternative materials used in the components, meeting the performance, functional requirements and reducing the environmental impact associated with the product life cycle. The investigation was carried out in monoblock pump impeller subassembly component. The environmental impact of CO2, SO2, PO4, ADF, and DCB has been evaluated using Centrum VoorMilieukunde Leiden (CML) methodology during the product's life cycle from raw material acquisition through production, end-of-life treatment recycling and final disposal (i.e. cradle – to grave). The reduction in pollutant emission and environmental impact categories was observed to be reduced by 40% of CO2, 37% of SO2, 39% of PO4 and 5% of DCB respectively. The numerical simulation test report proved that change of material will increases the life-span and efficiency of the pump, since significant reduction in deformation and stress intensity is obtained when compare with the existing material.